Human Nature: Terapihaven Nacadia som modernitetsretræte - Breunig, Malene (K&K - Kultur og Klasse, 2021)
The research-based Danish therapy garden Nacadia, which opened in 2011, can be viewed as a holistically oriented realization of the World Health Organization’s (WHO) broad definition of health from 1948: health is not just the absence of disease, but a state of both physical, mental and social well-being in which individuals may develop their abilities, deal with everyday challenges and stress, as well as socialize with other people. Nacadia’s raison d’être and relevance are indisputable. But the questions this article addresses are what perception of nature the therapy forest garden promotes and what social diagnosis it springs from and reproduces. Nacadia’s interdisciplinary research team provides no explanation, but these questions inform my analysis. Based on Nacadia’s concept manual and the therapy garden itself, as well as some literary accounts of engaging with nature, I develop two answers: First, that the researchers behind Nacadia operate with both a discourse and a physical-aesthetic presentation of nature as a peaceful and accessible place for both self-immersion and connection with ‘something greater’. Secondly, the implementation of such a sanctuary encourages romantically tinted modes of experience which certainly seem invigorating but may also evoke an element of alienation for people in a modern society.